Cajun justice [large type] - Patterson, James, 1947-; Axum, Tucker (Grand Central Publishing, 2020)
"Cain Lemaire is an ex-Secret Service agent from New Orleans. With help from his sister who's working in Japan, Cain takes a job in Tokyo as head of security detail for a very successful and important CEO. [He] ends up tangling with the yakuza (Japanese mafia) and unraveling a sex slavery ring"--